THE INFLUENCE OF SOCIAL MEDIA ON CUSTOMER SATISFACTION OF THE SAVEONE MARKET, NAKHON RATCHSIMA - Treepojana, Pawanrat; Inthasang, Chatchai; Thiamjit, Piyamaporn (Journal of Liberal Arts and Management Science Kasetsart University, 2020)
The objective of this research is to examine the relationship between effects of social media and customer satisfaction in the Saveone market, Nakhon Ratchasima. This research was conducted using quantitative approach by collecting questionnaires from 400 people. Number of customers was being selected by simple random sampling. This research analyzes the data using descriptive statistics method and multiple regressions for hypotheses testing. The results demonstrate that social media (Facebook and YouTube) a significant and positive effect on customer satisfaction. The study indicate that executives of business can implement and should understand social media in order to communicate effectively and fulfill customer needs. Therefore, managers have to keep themselves updated about what customers are interested, offers advantageous campaigns, and offers prevalent contents. However, conclusion and discussion include directions for future research are discussed in the last section of this research.